The functional characterisation of the XhABFA transcription factor from the resurrection plant Xerophyta humilis - Proctor, Jessica Diane (Department of Molecular and Cell Biology, 2021)
Vegetative desiccation tolerance (VDT), the ability to survive loss of up to 95% of cellular water in leaves and roots, is rare amongst vascular plants. However, the trait has evolved multiple times in a small, diverse group of angiosperms collectively known as “resurrection plants”. The physiological, morphological and metabolic changes that take place during VDT have been well characterised. However, in stark contrast, the underlying regulatory mechanisms that activate the VDT programme are not well understood. A widely held view is that VDT in resurrection plants may have arisen by a genetic reprogramming of the seed maturation pathways common to the vast majority of angiosperms. In Arabidopsis thaliana, the activation of seed maturation genes is regulated by the canonical LAFL (LEC1, ABI3, FUS3 and LEC2) network of transcription factors (TFs). However, thus far there is limited evidence to indicate that the LAFL network itself regulates VDT in resurrection plants, though downstream components of this network (such as the ABI3 regulon) are active. Recently, in a transcriptomic study of the resurrection plant Xerophyta humilis, it was found that the LAFL TFs are induced during seed maturation but not during vegetative desiccation. Instead, members of the ABF family of TFs, which are associated with the vegetative abiotic stress response, were strongly upregulated, particularly XhABFA. This finding supports an alternative hypothesis: namely that the activation of VDT in X. humilis has evolved by the rewiring of the transcriptional network that controls the abiotic drought stress response in desiccation sensitive plants. The aim of this study was to investigate whether XhABFA is able to bind to the promoters of and activate the expression of three genes, XhPER1, XhECP63 and XhDSI-1VOC, which are seed-specific in desiccation sensitive plant species but are upregulated in X. humilis leaves as they desiccate. Two experimental approaches were taken in order to determine this: transient expression of XhABFA in A. thaliana protoplasts transfected with promoter:firefly luciferase reporter constructs, and a Yeast One-Hybrid analysis. A. thaliana protoplasts expressing XhABFA displayed significantly greater firefly luciferase activity than protoplasts transfected with the empty vector, indicating that XhABFA can drive transcription from the promoters of these three canonical seed genes. This is the first evidence of activation of seed-specific genes in desiccating leaves by a “vegetative” abiotic stress TF and suggests that components of the drought stress response may be important in activating VDT in X. humilis. This finding may help shed light on our understanding of the regulatory networks underpinning VDT in angiosperm resurrection plants.